Performance of an implantable loop recorder in the detection of heart rhythm disturbances in patients with syncope and embolic strokes. (25th November 2020) - Kremer, M; Stierle, D.S; Naegele, H
Abstract: Aims: The primary goal of this study was the evaluation of the arrhythmia detection performance of an implantable loop recorder (ILR) in patients with syncope of unknown etiology and patients with embolic stroke of undetermined source (ESUS). Secondary goals were the evaluation of diagnostic yield, time to diagnosis and established therapeutical consequences. Methods: The Reveal LINQ ILR was implanted in n=143 patients (n=84 after ESUS, n=59 after syncope). Automatically detected episodes (n=3213) were transmitted via internet and validated by two experienced cardiologists and either classified as correct or incorrect. Positive-predictive value (ppv = true-positive episodes/true-positive episodes + false-positive episodes) was calculated for each available arrhythmia type. Incorrect episodes were classified as undersensing, oversensing, artifacts or supraventricular/ventricular ectopic beats. The diagnostic yield was defined by asystole ≥3 seconds or the detection of atrial fibrillation. Time to diagnosis was calculated as the time from implantation to detection of an asystole or atrial fibrillation. Results: Every second asystole episode in syncope-patients was false-positive (ppv 52%), mostly due to undersensing. The atrial fibrillation detection performance in ESUS-patients was 70% (ppv-average). The majority of false-positive episodes was due to premature atrial and ventricular complexes (80%), followed by artifacts (14%) and oversensing (4%). Undersensing accounted for 2%. 36% of syncope-patients were diagnosed with an asystole after a mean time to event of 114 days. In 47% of syncope-patients diagnosed with asystole, a pacemaker was implanted. In 31% of ESUS-patients a diagnosis of atrial fibrillation was established, after a mean time to event of 92 days. 85% of ESUS-patients diagnosed with atrial fibrillation were ultimately treated with an oral anticoagulant. Conclusion and discussion: The Reveal Linq ILR - advertised as an automatic diagnostic tool for syncope- and ESUS-patients - has its caveats. A high number of false-positive detections due to undersensing limited the asystole detection performance. The atrial fibrillation detection performance presented more reliable, despite a substantial number of false-positive detections. A time-consuming manual episode review still represents an indispensable step in the diagnostic process, and enough human resources have to be factored before starting an ILR program. Funding Acknowledgement: Type of funding source: None